Combined antihypertensive effect of unripe Rubus coreanus Miq. and Dendropanax morbiferus H. Lév. Extracts in 1 kidney-1 clip hypertensive rats and spontaneously hypertensive rats - Soyi Park; Ki Hoon Lee; Hakjoon Choi; Goeun Jang; Wan Seok Kang; Eun Kim; Jin Seok Kim; Chang-su Na; Sunoh Kim (BMC, 2021)
Abstract Background We previously showed that enzymatically hydrolyzed Dendropanax morbiferus H. Lév. leaf (Hy-DP) and unripe Rubus coreanus Miq. (5-uRCK) extracts exhibit potent vasodilator effects on isolated aortic rings from rats partly through endothelium-dependent and endothelium-independent mechanisms. These two extracts have different mechanisms of action; however, their combined effect on antihypertensive activity has not been explored. Methods The present study aims to investigate the effect of a chronic optimized mixture (HDR-2, composed of Hy-DP and 5-uRCK in a 2:1 mass ratio) on vascular tension and blood pressure in two different hypertensive rat models. Results The results showed that HDR-2 concentration-dependently relaxed endothelium-intact and endothelium-denuded aortic rings precontracted with phenylephrine. Antihypertensive effects were assessed in vivo on a 1 kidney-1 clip (1 K-1C) rat model of hypertension and spontaneously hypertensive rats (SHRs). Acute HDR-2 treatment significantly decreased systolic blood pressure (SBP) 3 h posttreatment in both models. Chronic HDR-2 administration also significantly decreased SBP in the hypertensive rat models. Moreover, HDR-2 increased eNOS protein expression and phosphorylation levels in the aorta. Conclusion Chronic HDR-2 administration may effectively improve vascular function by decreasing plasma angiotensin-converting enzyme (ACE) activity and AngII levels. HDR-2 significantly improved acetylcholine (ACh)-induced aortic endothelium-dependent relaxation and affected sodium nitroprusside (SNP)-induced endothelium-independent relaxation in SHRs.